Unlocking Cultural Nuances: Mastering Phraseological Unit Translation - Yusufjonova Shakhlo Mukhtorovna (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the challenges and complexities in translating phraseological units between languages, focusing on the differences between Uzbek and European languages. The main objective is to establish equivalence relations between linguistic units, taking into account semantic, stylistic, and visual aspects. To achieve this, the research identifies the categorical features of phraseological units, explores their structural-semantic and functional-stylistic features, and examines the role of national-cultural characteristics in translation processes. The study proposes five principles for translating phrasebooks and analyzes the common and distinct features of German and Uzbek proverbs. The results highlight the importance of a thorough understanding of linguistic units and national-cultural aspects in order to create accurate and effective translations, bridging the gap between languages and cultures. Highlights: Establishing equivalence relationships is crucial for successful translation of phraseological units, given their figurative meanings and cultural ties. A deep understanding of linguistic nuances, historical and cultural context, and the unique characteristics of phrasebooks is essential for accurate translation. Further research into the structural, functional, and cultural aspects of phraseological units can enhance translation techniques, benefiting the global linguistic community.